Inexact Newton regularization combined with two-point gradient methods for nonlinear ill-posed problems*This research is partially supported by NSFC grant 11971408 and NSFC/ANR joint program 51661135011/ ANR-16-CE40-0026-01. (8th March 2021) - Fan, Bin; Xu, Chuanju
Abstract: In this paper, we propose an inexact Newton regularization combined with two-point gradient methods for nonlinear ill-posed problems. The basic idea of the proposed method is to linearize the equation around each outer iteration and subsequently apply a so-called two-point gradient method in the inner loop to accelerate the iterative process. Under suitable assumptions, we show that the iteration sequence generated by the proposed algorithm converges to a solution of the related problem in the noiseless situation. Furthermore, the stability and regularization properties of the proposed algorithm are analyzed in the noise-data case. Several numerical examples are provided to validate the theoretical results and to demonstrate the efficiency of the proposed method.